Evaluation of cold storage effect on Murrah buffalo milk yoghurt quality and safety attributes through fourier transform infrared spectroscopy and multivariate analysis - Mansor, Muzammeer; Zulkifli, Afiefah; Mohamad Lotfi, Anis Ruwaida; Abdullah Sani, Muhamad Shirwan; Al-Obaidi, Jameel R.; Nor-Khaizura, Mahmud Ab Rashid; Khatib, Alfi; Abdull Razis, Ahmad Faizal; Meor Hussin, Anis Shobirin; Selamat, Jinap; Jambari, Nuzul Noorahya (Elsevier Ltd, 2025)
Buffalo milk yoghurt is valued for its flavour, nutrition, and health benefits, but storage conditions affect its quality. This study assessed physicochemical and microbiological changes in buffalo milk yoghurt during cold storage (4 ◦C) using FTIR spectroscopy and multivariate analysis. A commercial starter culture was inoculated into standardised buffalo milk, and samples were collected at six time points (0, 24, 48 h, 7, 14, and 28 days). Analyses included colour, texture, syneresis, pH, titratable acidity, water activity, and microbial counts. FTIR-OPLS-DA effectively discriminated storage times (Q2 = 0.91, R2Y = 0.979). Over time, redness (a*), yellow-ness (b*), consistency, and syneresis changed significantly, while lightness (L *) and firmness remained stable. Cohesiveness and work of cohesion decreased after 28 days. Lactic acid bacteria and total aerobic bacteria increased post-fermentation, with titratable acidity rising from 0.16 ± 0.02 to 1.64 ± 0.08 and pH dropping to 4.10 ± 0.01. These findings highlight the impact of cold storage on yoghurt quality and the effectiveness of FTIR spectroscopy for rapid assessment.